Ketidakhadiran Guru Hubungannya Terhadap Kerusakan Fasilitas Kelas dalam Jangka Waktu Satu Semester (Penelitian di SMP Darul Falah Cihampelas Bandung Barat) - Murharyana (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine how much influence the absence of teachers in teaching and learning activities (KBM) had on the damage to existing facilities in the classroom at SMP Darul Falah Cihampelas West Bandung. The number of teachers in this school is 110 people and the number of students is 27 groups with grade 7 nine grades, grade 8 nine classes, and grade 9 nine classes, teacher attendance was studied in the odd semester of the 2018-2019 school year, with a presentation of 100% attendance in January , February 96%, March 98%, April 70%, May 98% and June 50%. From these data, the level of influence of the teacher's presentation with the damage to class facilities will be presented.